Developmental Biology Protocols : Volume I - Lo, Cecilia W. (Totowa, NJ : Humana Press Inc., 2017)
The molecular biology revolution has transformed developmental biology into one of the most exciting and fruitful fields in experimental biomedical research today. In Developmental Biology Protocols, established leaders in this field demonstrate this achievement with a comprehensive collection of cutting-edge protocols for studying and analyzing the events of embryonic development. Drawing on state-of-the-art cellular and molecular techniques, as well as new and sophisticated imaging and information technologies, this first volume of three presents readily reproducible methods for establishing and characterizing several widely used experimental model systems, for both the study of developmental patterns and morphogenesis, and the examination of embryo structure and function. In addition, there are step-by-step methods for the analysis of cell lineage, the production and use of chimeras, and the experimental molecular manipulation of embryos, including the application of viral vectors (...)